Islet–immune interactions in type 1 diabetes: the nexus of beta cell destruction. (14th August 2019) - Peters, L.; Posgai, A.; Brusko, T. M.
Summary: Recent studies in Type 1 Diabetes (T1D) support an emerging model of disease pathogenesis that involves intrinsic β‐cell fragility combined with defects in both innate and adaptive immune cell regulation. This combination of defects induces systematic changes leading to organ‐level atrophy and dysfunction of both the endocrine and exocrine portions of the pancreas, ultimately culminating in insulin deficiency and β‐cell destruction. In this review, we discuss the animal model data and human tissue studies that have informed our current understanding of the cross‐talk that occurs between β‐cells, the resident stroma, and immune cells that potentiate T1D. Specifically, we will review the cellular and molecular signatures emerging from studies on tissues derived from organ procurement programs, focusing on in situ defects occurring within the T1D islet microenvironment, many of which are not yet detectable by standard peripheral blood biomarkers. In addition to improved access to organ donor tissues, various methodological advances, including immune receptor repertoire sequencing and single‐cell molecular profiling, are poised to improve our understanding of antigen‐specific autoimmunity during disease development. Collectively, the knowledge gains from these studies at the islet–immune interface are enhancing our understanding of T1D heterogeneity, likely to be an essential component for instructing future efforts to develop targeted interventions to restore immune tolerance and preserve β‐cell mass and function. Abstract :